Planowanie zajęć dydaktycznych na studiach wyższych w okresie pandemii - Lisowska, Kinga (Kultura-Społeczeństwo-Edukacja, 2022)
The article focuses on the issue of preparing the schedule of didactic classes in the conditions of social isolation and sanitary regime during the COVID-19 pandemic at universities in Poland. The research was conducted at the Faculty of Social Sciences, University of Warmia and Mazury in Olsztyn, based on individual interviews, partially directed, with employees responsible for planning in 2017 2021, analysis of existing databases, i.e. state-wide regulations and intra-university regulations. To elaborate on the subject, an outline of the pre-pandemic timetable preparation process was outlined and compared with planning in times of complete isolation and recovery to relative normality in a sanitary regime. The preparation of a relevant timetable of didactic classes, taking into account study plans for individual fields of study for the entire education cycle, is a time-consuming and responsible work, in which the margin of error should be minimized in: overlapping the implementation of didactic units and hourly miscalculation of individual subjects. This task in the period of isolation and relative stabilization in the sanitary regime was a huge challenge for planners, who often had to react to a dynamically changing pandemic situation. Inefficient preparation of timetables can significantly disrupt the organization of the didactic process in higher education.